Quality management effectiveness in Asia: The influence of culture - Kull, Thomas J.; Wacker, John G. (Journal of Operations Management, 2010)
AbstractGlobalization forces managers to utilize manufacturing capabilities from countries with different cultures than their own, particularly from Asia. Yet quality problems in China have raised concerns among managers and researchers as to how to assure product quality from Asian facilities. Implementing quality management practices may accomplish this, but such practices assume specific cultural values exist in certain Asian cultures. Using global manufacturing and cultural data, this study examines if cultural values in Asian and non‐Asian countries moderate how effective quality management practices are at improving quality performance. Through the use of multilevel modeling, differences in quality management effectiveness are found among the East Asian cultures of China, South Korea, and Taiwan. Moreover, this study finds that specific cultural dimensions are statistically related to quality management effectiveness. The results of this study will assist managers in devising plans to assure higher quality from East Asian facilities and in predicting where problems may occur in other countries around the world.